Architecting federations of systems: A framework for capturing synergy. Issue 4 (13th March 2019) - Lluch, Ignasi; Golkar, Alessandro
Abstract: This paper defines Federations of Systems, introduces a tailored architecting framework, and demonstrates it in a satellite design case study. While certainly not being new concepts in the literature, federations are a class of Systems of Systems (SoS) that have not been extensively explored due to the scarcity of applied examples and still few practitioners facing their specific design challenges. This is expected to change with the advent of the Internet of Things, Machine to Machine applications, collaborative consumption, and Federated Satellite Systems. It has become henceforth necessary to develop approaches in design and architecting capable of addressing such interconnected sets of systems. Federations are SoS characterized by the absence of global goals and stakeholders, and cooperation enabled only on an opportunistic basis. Systems engage in federations when the perceived benefit exceeds the costs of the necessary interfaces. The proposed framework quantifies the upper limits to the net benefits of cooperation between systems through the concept of synergy. Using synergy as a heuristic to navigate federated design spaces, the framework predicts the appearance and evolution of federations. The demonstration of the framework in a six‐satellite federation shows that advantages of federating emerge with the collaboration between just two systems. Interface costs, architectural cost preferences, and network topology drive the achievable benefits. Specifically, when considering communication architectures under 80 MUSD for satellite systems, federating is advantageous when the interface lifecycle costs are below 15 MUSD. This demonstration case exemplifies how federating can assist systems in achieving design points that dominate the solutions of their local tradespace.